Modified Constraint-Induced Therapy Combined With Mental Practice: Thinking Through Better Motor Outcomes - Page, Stephen J.; Levine, Peter; Khoury, Jane C. (Stroke (1970), 2009)
BACKGROUND AND PURPOSE—Modified constraint-induced therapy (mCIT) is an outpatient therapy encouraging repetitive, task-specific practice with the affected arm. mCIT has shown efficacy in all stages poststroke. Given its efficacy when combined with other therapy regimens, the current study examined the efficacy of mental practice when combined with mCIT versus mCIT only using randomized, controlled methods. METHOD—Ten patients with chronic stroke (7 males; mean age, 61.4±3.02 years; age range, 48 to 79 years; mean time since stroke, 28.5 months; range, 13 to 42 months) exhibiting stable, affected arm motor deficits were administered mCIT, consisting of(1) structured therapy emphasizing affected arm use in functional activities 3 days/week for 10 weeks; and (2) less affected arm restraint 5 days/week for 5 hours. Both of these components were administered during a 10-week period. Subjects randomly assigned to the mCIT+mental practice experimental condition also received 30-minute mental practice sessions provided directly after therapy sessions. These mental practice sessions required daily cognitive rehearsal of the activities of daily living practiced during mCIT clinical sessions. RESULTS—No pre-existing differences were found between groups on any demographic variable or movement scale. All subjects exhibited marked reductions in affected arm impairment and functional limitation. However, subjects in the mCIT+mental practice group exhibited significantly larger changes on both movement measures after interventionAction Research Arm Test, +15.4-point change versus +8.4-point change for mCIT only subjects (P<0.001); Fugl-Meyer, +7.8-point change versus +4.1-point change for the mCIT only subjects (P=0.01). These changes were sustained 3 months after intervention. CONCLUSIONS—mCIT remains a promising motor intervention. However, its efficacy appears to be enhanced by use of mental practice provided directly after mCIT clinical sessions.